2013
DOI: 10.1088/0256-307x/30/12/129501
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleon Direct Urca Processes in a Cooling Neutron Star

Abstract: In the relativistic mean field approximation, the relativistic energy losses of the nucleon direct Urca processes are studied in the degenerate baryon matter of neutron stars. We investigate the effects of hyperon degrees of freedom and the isovector scalar interaction which is considered by exchanging 𝛿 meson on the nucleon direct Urca processes in neutron star matter. The results indicate that the existence of hyperons decreases the abundance of protons and leptons and can sharply suppress the neutrino emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…When the density is larger than 2-3 times the saturation density, hyperons appear in the neutron stars [6]. References [7][8][9][10][11] have studied the effects of hyperons on the N-DURCA process and suggested that the existence of hyperons can reduce the neutrino emissivity of the N-DURCA process. The hyperon direct URCA process also exists once the Λ hyperon appears [12].…”
Section: Introductionmentioning
confidence: 99%
“…When the density is larger than 2-3 times the saturation density, hyperons appear in the neutron stars [6]. References [7][8][9][10][11] have studied the effects of hyperons on the N-DURCA process and suggested that the existence of hyperons can reduce the neutrino emissivity of the N-DURCA process. The hyperon direct URCA process also exists once the Λ hyperon appears [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the most powerful enhancement of neutrino emission is provided by the nucleon direct Urca processes (NDUP), secondarily is the hyperon direct Urca processes (HDUP) [21][22][23][24][25][26][27][28]. Besides, the degrees of freedom of hyperons tend to soften the equation of state (EOS) calculated in the relativistic mean field (RMF) model based on SU (6) spin-flavor symmetry(quark model for the vector meson-hyperon coupling constants), then reduce the maximum mass of NS to about 1.6-1.7M ⊙ [29][30][31][32][33][34][35]. However, Demorest et al in 2010 [36] indicated that the binary millisecond pulsar PSR J1614-2230 expanded the maximum observational mass from 1.67 ± 0.02M ⊙ to 1.97 ± 0.04M ⊙ using the Shapiro delay measurements from radio timing observations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have been focussing on 1 S 0 protonic superfluidity. Since the protonic superfluid states as well as their pairing strength can greatly suppress the neutrino processes involving nucleons about 10 5 − 10 6 years of NS cooling phases, affect the properties of rotating dynamics, post-glitch timing observations and possible vertex pinning of NSs [14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%